2009
DOI: 10.1111/j.1464-410x.2009.08420.x
|View full text |Cite
|
Sign up to set email alerts
|

The number of procedures required to achieve optimal competency with male circumcision: findings from a randomized trial in Rakai, Uganda

Abstract: OBJECTIVE To assess the number of procedures required to achieve optimal competency (time required for surgery with minimal adverse events) in Rakai, Uganda, and thus facilitate the development of guidelines for training providers, as male circumcision reduces the acquisition of human immunodeficiency virus (HIV) in men and is recommended for HIV prevention. PATIENTS AND METHODS In a randomized trial, 3011 men were circumcised, using the sleeve method, by six physicians who had completed training, which includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…RCTs have shown that more experienced providers perform faster and safer circumcisions, 8,22 and our results confirm these findings. In our study, the providers who had performed only 20 male circumcisions under supervision took an average of 21.0 minutes to perform their first 20 procedures; however, providers who had performed more than 100 circumcisions and those who had performed over 200 procedures took an average of 17.6 and 15.5 minutes, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…RCTs have shown that more experienced providers perform faster and safer circumcisions, 8,22 and our results confirm these findings. In our study, the providers who had performed only 20 male circumcisions under supervision took an average of 21.0 minutes to perform their first 20 procedures; however, providers who had performed more than 100 circumcisions and those who had performed over 200 procedures took an average of 17.6 and 15.5 minutes, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…This study lends support to recommendations that providers must perform a minimum of 20 male circumcision procedures to qualify as a VMMC provider, and ideally over 100 procedures to reach and maintain a desired level of clinical expertise. 8,22 In Kenya, legislation was passed in 2009 to allow nurses to provide VMMC services as part of the national VMMC programme. While adjusting for provider experience reduced the magnitude of the protective effect conferred by having a clinician rather than a nurse perform the circumcision, in the clinic system a procedure performed by a clinician was still 40.0% less likely to result in an adverse event than one performed by a nurse.…”
Section: Discussionmentioning
confidence: 99%
“…It would be instructive to look at the nature of training obtained, total number of cases performed and the complication rates among the trainees, as this may give objective insight into the actual level of competence in the NC procedure. Although a study has suggested that performing at least 100 circumcisions is required before some Evaluation of neonatal circumcision training 1.e3 + MODEL measure of competence is assured for male circumcision [16], this alone is insufficient. Concerning training in surgical procedures, several studies have shown that well-structured training, which encompasses a good theoretical knowledge base and practical exposure to a specific surgical procedure, is imperative to perform the procedure well and to diminish complications [15e18].…”
Section: Discussionmentioning
confidence: 99%
“…When presented with contraindications to circumcision like hypospadias, buried penis and micropenis, the average rate of correctly identified contraindications was a dismal 42%. Evidence from the Ugandan trial data showed that approximately 100 procedures are needed to gain competence in sleeve circumcision technique [231]. The rate of moderate or severe adverse events showed a statistically significant trend decreasing from 8.8% for the first 20 procedures to around 2% beyond 100.…”
Section: Training Implicationsmentioning
confidence: 98%